Layanan konseling sebagai Upaya pengembangan tugas perkembangan sosial pribadi Anak di sekolah Dasar - Nia Fitriani; Neng Ai Siti Minhatul Faridah; Teti Ratna Wulan (AL-IBANAH, 2025)
This study aims to analyze the implementation of counseling services in fostering the socio-personal development tasks of elementary school children at SDN 090 Cibiru. This mini-research specifically examines the role of counseling services in supporting students' socio-personal growth at the elementary school level, particularly within SDN 090 Cibiru. Using a qualitative case study method, data was collected from fourth-grade students, their homeroom teachers, and the Islamic Religious Education (PAI) teacher through interviews, observation, and documentation. The data was then analyzed interactively. The findings indicate that the existing services remain informal, largely teacher-led, and have limited impact. Supporting factors (school principal's support, teacher initiative) are offset by major hindering factors (minimal facilities/infrastructure, teacher workload, negative stigma) In conclusion, counseling services at SDN 090 Cibiru are not yet optimal due to resource limitations, informal structures, and collaboration challenges. Recommendations include strengthening service structures, developing comprehensive-preventive programs, enhancing collaboration, educating to remove stigma, and providing adequate facilities